Determinants of Farmers’ Use of Land Reclamation Practices in Oil Producing Areas of Imo State, Nigeria: Application of Multivariate Logistic Analysis - F.C, Anaeto; N, Okereke -Ejiogu; D.O, Ohajianya; C.O, Korie; N.F, Dike; P.C, Uke (Review of Plant Studies, 2017)
This study analyzed the determinants of farmer’s use of land reclamation practices in oil producing areas of Imo State, Nigeria. Data for the study were obtained with structured questionnaire from 172 food crop farmers selected through multistage sampling procedure. Descriptive statistics was used to determine the level of use of land reclamation practices, while inferential statistical technique (logit model) was used to estimate the determinants of farmers ‘use of land reclamation practice. Results showed low level of use of land reclamation practices (x =1.5) among the farmers, and land filling was better practiced than other land reclamation practices. Determinants of farmers ‘use of land reclamation practices were level of education, farm size, extension contact, annual farm income, social organization membership, availability of land reclamation technology, and access to information. In order for land reclamation practices to mitigate the land degradation and soil fertility loss experienced in the oil producing areas of Imo State, government should adequately motivate the extension personnel to follow-up the use of the introduced land reclamation practices by the farmers.